ADHD and mindfulness: Looking to Eastern thought to expand Western practice - Tiffany Devol; Qi Sun (Adult Education Research Conference, 2020)
This roundtable presents mindfulness exercise as a transformative approach in the teaching and learning process. It discusses how this ancient eastern meditation technique can holistically empower adult learners with Attention Deficit Hyperactivity Disorder (ADHD).
Keywords: Mindfulness; ADHD; Attention Deficit Hyperactivity Disorder